The Effect of YouTube Advertising and eWOM on Brand Awareness and Purchase Intention Among Millennial Consumers in Indonesia - Nufika Salsa Yiki; Imronudin Imronudin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the influence of YouTube advertising and electronic word-of-mouth (eWOM) on brand awareness and purchase intention among millennial consumers in Indonesia. This research is guided by the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM) to explain how digital marketing through YouTube ads and eWOM affects consumer behavior. The sample comprises 200 millennial consumers who actively use YouTube. Purposive sampling was employed to target individuals within this specific demographic. The study participants were aged 18–35 years, with varied educational backgrounds and income levels, providing insights into how these factors influence exposure to digital marketing and purchase decisions. Data analysis was conducted using Smart PLS software, with detailed testing for the validity and reliability of the measurement instruments. Specifically, the study examined factor loadings, average variance extracted (AVE), and composite reliability. Hypothesis testing results indicated a significant influence of YouTube and eWOM advertisements on brand awareness. Moreover, both YouTube and eWOM ads significantly impacted purchase intention among Indonesian millennials.